Associations of muscle-strengthening exercise with overweight, obesity, and depressive symptoms in adolescents: Findings from 2019 Youth Risk Behavior Surveillance system - Shi, Jizu; Gao, Mingjun; Xu, Xiao; Zhang, Xuyang; Yan, Jin (Frontiers in Psychology, 2022)
Background: Previous studies have mostly studied the opposite relation between muscle strength, obesity, and depression in adults, but the evidence to prove that obesity and depression in adults can be significantly reduced through muscle-strengthening exercise (MSE) is insufficient. Consequently, a cross-sectional study has been carried out in this paper, to determine the links between muscle strength exercise, obesity, and depression in American adults. Methods: In YRBS, a cluster sample was used and the investigation was divided into 3 stages. Totally 13,677 high school students participated in the study and conducted self-management. The study gets the nationally representative population of American students in Grade 9 to 12 (around 12-18 years). Results: The participants meeting the requirements of the guidelines seem more likely to be obese than those who don’t meet (OR=1.28, 95% CI= 1.06-1.55). For the full model, there was no statistical significance in the relations between MSE guidelines and overweight and depression (OR=0.86, 95% CI=0.73-1.01: OR=0.94, 95% CI=0.83-1.06). The overall response rate (students and schools) was 60%. The purpose of samples in YRBS was to provide accurate estimates (± 5%) at the confidence level of 95%. For all the participants, the prevalence of those conforming to MSE was 30.1%. In the designed sample, girls account for 50.3% (n=6885) and boys take up 48.6% (n=6641), among which the population of Grade 10 was the largest (27.2%). One-fifth of the participants reported no MSE per week, 7.8% reported three days of MSE per week and 7.7% reported seven days. Conclusion: The main finding of this study indicated that there existed a positive relationship between the normative MSE as required in guidelines and lower level of obesity, while it did not exist between the duration of exercise and lower prevalence of obesity in American youth. In addition, the proof was insufficient to confirm the positive links between MSE and depression among US adolescents.